1976
DOI: 10.1113/expphysiol.1976.sp002351
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Regional Lymphatic System of the Sheep to Acute Stress and Adrenaline

Abstract: An acute pain stimulus resulted in elevated lymph flow and output of cells from the popliteal lymph node of the sheep in the first 15 min after the stress. Efferent lymph flow increased by an average of 93 % above the mean resting flow and cell output rose by an average of 170% during this period, but by 30 min after the stress, values for both lymph flow and cell output had returned to normal. The cell content of the efferent lymph was significantly higher in the first 15 min after the acute stress and it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

1980
1980
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…This response was undoubtedly a complex one involving many factors other than reflex sympathetic activation since attempts to mimic it by inducing cerebral ischaemia re sulted in a much smaller increase in pump ing activity [29], Emotional Stress. Shannon et al [30] and McHale and Roddie [31] observed that sheep hind limb lymph flow increased when the animals were startled. They suggested that this might be due to a nervous reflex but the results were difficult to interpret since the animal sometimes moved when it was frightened and this in itself is known to increase hind limb lymph flow.…”
Section: Lymphomotor Reflexesmentioning
confidence: 99%
“…This response was undoubtedly a complex one involving many factors other than reflex sympathetic activation since attempts to mimic it by inducing cerebral ischaemia re sulted in a much smaller increase in pump ing activity [29], Emotional Stress. Shannon et al [30] and McHale and Roddie [31] observed that sheep hind limb lymph flow increased when the animals were startled. They suggested that this might be due to a nervous reflex but the results were difficult to interpret since the animal sometimes moved when it was frightened and this in itself is known to increase hind limb lymph flow.…”
Section: Lymphomotor Reflexesmentioning
confidence: 99%
“…Depending on the catecholamine infused, subject, and dosage, biphasic leukocytosis is observed that is comprised of a marked neutrophilia and lymphocytosis, and is followed by a delayed lymphopenia (Burns et al 1997). However, the results examining the effects of Epi on the lymphatic system have been contradictory (Iveson et al 1994;Shannon et al 1976;Steel et al 1971). Therefore, we designed experiments to examine the effects of Epi on lymph volume, cell output, and lymphocyte subsets.…”
Section: Introductionmentioning
confidence: 99%
“…McHale & Thornbury (1986) demonstrated a threefold increase in volume of fluid pumped when the sheep's head was held for a period of 1 min. Similarly Shannon, Quin & Jones (1976) showed that lymphocyte output in efferent lymph, as well as lymph flow, was increased in response to painful stimuli. Thus it may be that the role of lymphatic innervation is concemed more with the immunological functions of the lymphatic system than with fluid homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it may be that the role of lymphatic innervation is concemed more with the immunological functions of the lymphatic system than with fluid homeostasis. The present study seeks to establish whether the sympathetic nervous system can mimic the lymphocytosis in response to an acute pain stimulus reported by Shannon et al (1976).…”
Section: Introductionmentioning
confidence: 99%